On the optimal coding of one class of vector functions - Polovina, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We consider the problem of coding of parametrically defined vector functions by continuous functionals which act on their coordinate functions. We obtain the optimal method for coding some class of vector functions. In the linear case, we show the relation between this method and the informativeness of functionals with respect to the class of coordinate functions.